Engineering of epidermis skin grafts using electrospun nanofibrous gelatin/polycaprolactone membranes - Duan H (Dove Medical Press, 2013)
Huichuan Duan,1,* Bei Feng,2,* Xiangkai Guo,3 Jiaming Wang,1 Li Zhao,1 Guangdong Zhou,1 Wei Liu,1 Yilin Cao,1 Wen Jie Zhang1 1Department of Plastic and Reconstructive Surgery, Shanghai 9th People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai Key Laboratory of Tissue Engineering, National Tissue Engineering Center of China, Shanghai, People’s Republic of China; 2Department of Cardiothoracic Surgery, Institute of Pediatric Translational Medicine, Shanghai Children’s Medical Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3School of Medicine and Life Sciences, University of Jinan-Shandong Academy of Medical Sciences, Ji Nan, Shan Dong, People’s Republic of China *These authors contributed equally to this work Abstract: Skin engineering provides a new strategy for treating a wide variety of skin defects. In particular, electrospun nanofibrous membranes have been used as carriers for epidermis engineering. The aim of this study was to investigate the feasibility of a modified gelatin and polycaprolactone (GT/PCL) electrospun membrane for epidermis engineering. The biocompatibility of the membranes was evaluated by seeding HaCaT cells (human keratinocyte cell line) on the membrane and the mechanical properties of the membranes were determined with and without cells after culture. A cell proliferation assay showing that HaCaT cells attached and proliferated well on the membranes demonstrated that the membranes possess good biocompatibility. Mechanical tests showed that the membranes are strong enough to be handled during transplantation. Further in vivo transplantation studies revealed that epidermises engineered with GT/PCL membranes were able to repair skin defects in the nude mouse. These results demonstrate that GT/PCL electrospun membranes could be suitable scaffolds for skin engineering. Keywords: epidermis engineering, electrospun nanofibrous membrane, gelatin, polycaprolactone